Persepsi ibu dalam pemberian makanan tambahan pada bayi di Puskemas Pembantu Desa Joho wilayah kerja Puskesmas Pace Kabupaten Nganjuk - siti maemonah (FORUM ILMIAH KESEHATAN, 2016)
MOTHER’S PERSEPTION OF SUPPLEMENTARY FEEDING FOR INFANT IN PUBLIC HEALTH ASSISTANT OF JOHO VILLAGE WORKING AREA PACE’S PUBLIC HEALTH NGANJUK Siti Maemonah, Ahmad Abi Lahabi (Program Studi D3 Keperawatan Kampus Sidoarjo) sitimaemonah71@yahoo.com Perception of a mother in feeding their babies may differ perhaps also the same as anyone else. This is because many factors affect a person's perception. The purpose of this study was to determine the perceptions of mothers in infant feeding in rural health centers Joho the pace of work centers Nganjuk district. In this study the method used is qualitative in-depth interview technique (depth interview). Informants were mothers who come to the village health centers Joho. The number of informants 10 people consisting of mothers who now have children younger than 1 year. The interviews were analyzed qualitatively by comparing the informant answers that include the theme of supplementary feeding with a theory that has been obtained from the literature. From this study it can be concluded that the perception of women in supplementary feeding is given butter milk food, food that is given as breast milk, food that is given when the infant cries, the food given as an infant, was given when aged less than 6 months or more than 6 months in order for a large fast infant, infant is not fussy, adequate nutrition, good development, and prevent malnutrition. Expected to be more attention again to the local health workers for about providing health education on a regular basis about infant feeding for mothers to find out how the provision of supplementary food is good and right so it will not interfere with the baby's health Key words: perception, supplementary feeding, infant